D.B. MacMillan (1874-1970) - Baird, P.D. (ARCTIC, 1971)
D.B. MacMillan, "Captain Mac", is no longer with us. As an Arctic sailor and oldtime sled driver he ranked with the greats of northern skippers. . An iron body, conditioned by early gymnastic effort and sustained until the age of fourscore by conning his ship through the ice, kept him hale and mentally active until the end of 95 years. . He was teaching school, inspiring his pupils in the Maine woods with a love of botany and geology, when Peary asked him to join his assault on the Pole in 1908. . From [then] on the Arctic was his life. He started planning a new expedition with his Roosevelt cabin mate Borup in 1911, but Borup died, and it was 1913 before he got away on the "Crockerland Expedition". His "Four Years in the Frozen North" tells the tale of this project. . In 1920 MacMillan commissioned the famous vessel Bowdoin named after his Maine college, a 60-ton auxiliary wooden schooner designed to buck ice in arctic waters. First he took a scientific party to southwest Baffin Island, then to Northwest Greenland, wintering on both occasions. . The war years saw Bowdoin taken over by the U.S. Navy. At first MacMillan was her skipper, but later he was moved to a consultative desk job with the Hydrographer while others, less competent, did their best to ruin his stout schooner. But he was able to reclaim her and refit her after the war, and at the age of eighty was still sailing north. .